Optimization and Characterization of Silver Nanoparticle by Endophytic Fungi Penicillium sp. Isolated from Curcuma longa (Turmeric) and Application Studies against MDR E. coli and S. aureus - Dattu Singh; Vandana Rathod; Shivaraj Ninganagouda; Jyothi Hiremath; Ashish Kumar Singh; Jasmine Mathew (Bioinorganic Chemistry and Applications)
Development of ecofriendly and reliable processes for the synthesis of nanoparticles has attracted considerable interest in nanotechnology because of its tremendous impetus in modulating metals into nanosize to their potential use for human benefits. In this study an endophytic fungus, Penicillium sp., isolated from healthy leaves of Curcuma longa (turmeric) was subjected to extracellular biosynthesis of silver nanoparticles (AgNps) and their activity against MDR E. coli and S. aureus. The biosynthesized AgNps optimization was studied and characterized by UV-visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM). Then produced AgNps were tested against MDR E. coli and S. aureus. The endophytic fungus Penicillium sp. from healthy leaves of C. longa (turmeric) was found to be a good producer of AgNps. Parametric optimization showed maximum absorbance of 420–425 nm at pH-7, 25°C with 1 mM AgNO3 concentration and 15–20 g of wet biomass. Further TEM revealed the formation of spherical, well-dispersed nanoparticles with size ranging between 25 and 30 nm and FTIR shows the bands at 1644 and 1538 cm−1 corresponding to the binding vibrations of amide I and II bands of proteins, respectively. Antibacterial activity against MDR E. coli and S. aureus showed good results showing maximum zone of inhibition of 17 mm and 16 mm, respectively, at 80 µL of AgNps.